Sintilimab plus a bevacizumab biosimilar (IBI305) in advanced HCC with Child-Pugh A/B liver function: a real-world multicenter retrospective study - Zhang, Yuanxu; Miao, Youhan; Sun, Wei; Yu, Yixing; Wang, Jinjing; Xiao, Shuang; Lu, Shengwei; Wang, Xia; Li, Yang; Pan, Xiucheng; Zhao, Weifeng (Frontiers in Oncology, 2025)
BackgroundSintilimab plus a Bevacizumab biosimilar (IBI305) is an approved first-line regimen for unresectable hepatocellular carcinoma (uHCC) in China. However, data on its safety and efficacy in patients with impaired liver function remain limited. We assessed the clinical outcomes of this combination therapy in HCC patients with Child-Pugh class A (CP-A) and class B (CP-B) liver function.MethodsIn this multicenter retrospective cohort study, 99 patients with advanced uHCC (73 CP-A; 26 CP-B) who received first-line Sin/Bev were included. Tumor response was assessed using modified RECIST criteria, and adverse events (AEs) were graded per CTCAE v5.0. Survival outcomes, including overall survival (OS), progression-free survival (PFS), and time to hepatic decompensation (TTD), were analyzed via Kaplan-Meier estimates and Cox proportional hazards models.ResultsThe objective response rates (ORR) of patients with CP-A and CP-B treated with Sin/Bev were 50.7% and 57.7%, respectively, and both could achieve good anti-tumor efficacy. CP-B had inferior survival: median OS (15 vs 22 months, p=0.044), PFS (8 vs 14 months, p=0.014), and TTD (7 vs 15 months, p<0.001). The CP-B cohort demonstrated comparable incidence rates of grade 3–4 AEs to the CP-A group (34.6% vs 34.2%). Hemorrhagic events and thrombocytopenia emerged as predominant grade 3–4 AEs in CP-B patients (15.4% for both).ConclusionsSin/Bev demonstrated encouraging short-term anti-tumor activity in HCC of CP-A and CP-B, while survival outcomes were affected by differences in hepatic function. Although the regimen was generally well tolerated, patients with impaired liver reserve require vigilant monitoring and comprehensive supportive strategies to maximize therapeutic outcomes.